Consuming Life in Post-Bubble Japan : A Transdisciplinary Perspective - Cwiertka, Katarzyna J.; Machotka, Ewa (Amsterdam : Amsterdam University Press, 2018)
This multidisciplinary book analyzes the contradictory coexistence of consumerism and environmentalism in contemporary Japan. It focuses on the dilemma that the diffusion of the concepts of sustainability and recycling has posed for everyday consumption practices, and on how these concepts have affected, and were affected by, the production and consumption of art. Special attention is paid to the changes in consumption practices and environmental consciousness among the Japanese public that have occurred since the 1990s and in the aftermath of the earthquake, tsunami, and nuclear disasters of March 2011.
Frontmatter -- Table of Contents -- List of Figures and Tables -- Acknowledgements -- Notes to the Reader -- Introduction / J.Cwiertka, Katarzyna / Machotka, Ewa -- Post-Bubble Japanese Department Stores: The Need to Search for New Paradigms / Meyer-Ohle, Hendrik -- Consumption of Fast Fashion in Japan: Local Brands and Global Environment / Assmann, Stephanie -- Konbini-Nation: The Rise of the Convenience Store in Post-Industrial Japan / H. Whitelaw, Gavin -- Serving the Nation: The Myth of Washoku / J. Cwiertka, Katarzyna -- Consuming Domesticity in Post-Bubble Japan / Goldstein-Gidoni, Ofra -- The Metamorphosis of Excess: 'Rubbish Houses' and the Imagined Trajectory of Things in Post-Bubble Japan / Gygi, Fabio -- Robot Reincarnation: Rubbish, Artefacts, and Mortuary Rituals / Robertson, Jennifer -- Art and Consumption in Post-Bubble Japan: From Postmodern Irony to Shared Engagement / Borggreen, Gunhild -- The Fate of Landscape in Post-War Japanese Art and Visual Culture / Michio, Hayashi -- Consuming Eco-Art: Satoyama at the Echigo-Tsumari Art Triennale 2012 / Machotka, Ewa -- Artistic Recycling in Japan: Today A Curator's Perspective / Akiko, Kasuya -- Notes on Contributors -- Index
Mode of access: Internet via World Wide Web.
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 08. Jul 2019)
Keywords: HISTORY / General